World War II - Osborne, Mary Pope; Boyce, Natalie Pope (Magic tree house fact tracker., 2017)
Examines the historical events the Magic Tree House book "World at War, 1944" is based on, discussing the causes of the war and D-Day with photographs and illustrations.